2021
DOI: 10.1007/s10388-021-00850-0
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of nivolumab treatment in Japanese patients with esophageal squamous-cell carcinoma (ATTRACTION-1/ONO-4538-07)

Abstract: Background In the phase II ATTRACTION-1 study, nivolumab demonstrated a promising antitumor activity among Japanese patients with treatment-refractory advanced esophageal cancer. Here, we report the follow-up results of ATTRACTION-1 of > 5 years. Methods We enrolled patients with esophageal cancer that was refractory or intolerant to a standard chemotherapy. Then, nivolumab (3 mg/kg) was administered every 2 weeks. The primary endpoint was a centrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Nivolumab is also expected to be effective in the gastrointestinal field and has become an established treatment for gastric cancer ( 25 ). According to several reports, nivolumab improved the prognosis of patients with advanced or recurrent esophageal cancer, and it has been used in clinical practice in Japan since 2020 ( 6 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab is also expected to be effective in the gastrointestinal field and has become an established treatment for gastric cancer ( 25 ). According to several reports, nivolumab improved the prognosis of patients with advanced or recurrent esophageal cancer, and it has been used in clinical practice in Japan since 2020 ( 6 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICIs have become an extremely important treatment option for upper GIT cancers. Moreover, the management of Although it has been reported that patients with irAEs have a better prognosis in various carcinomas (13)(14)(15)(16)(17), for example non-small cell lung cancer and melanoma, the relationship between irAEs and treatment response in upper GIT cancer remains unclear. In this study of 96 upper GIT cancer cases, we found that the prognosis of both esophageal cancer and GC was better in patients with irAEs than in those without.…”
Section: Discussionmentioning
confidence: 99%
“…The development of irAEs is associated with survival in melanoma and non-small cell lung cancer, suggesting that early development of irAEs may predict better outcomes with ICIs and that prompt management of irAEs may prolong treatment duration and maximize the therapeutic effect of ICIs (9). Although several reports have shown that the occurrence of irAEs is associated with the prognosis of advanced GC treated with ICIs (10)(11)(12)(13), there are few reports on advanced esophageal cancer and, therefore, there are insufficient data in this regard (2,8,(10)(11)(12)(13). This study aimed to investigate the prognostic impact of irAEs in patients with advanced or recurrent upper GIT cancer treated with nivolumab.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression was observed in 18.4% to 82.8% of ESCC tumors and was related to a poor survival rate ( 34 ). In the ATTRACTION-1/ONO-4538-07 study, nivolumab significantly prolonged the OS period ( 35 ). Furthermore, when combined with chemotherapy, nivolumab can significantly improve OS and PFS ( 36 ), but hyperprogressive disease in elderly people and immune-related pneumonia still need to be considered ( 37 ).…”
Section: Discussionmentioning
confidence: 99%